Exergetic Analysis of Hybrid Photovoltaic - Thermal Solar Collectors Coupled to Organic Rankine Cycles = Analiza ekologiczna hybrydowego układu fotowoltaika - kolektory słoneczne związanych organicznym cyklem Ranking`a - Pinto, Clara; Mady, Carlos Eduardo (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this work, the application of hybrid solar modules that combine photovoltaic panels and solar thermal collectors coupled with a low-temperature thermal cycle such as the Organic Rankine Cycle is discussed, their main purpose being an increase in the total electric power production per available area.
Keywords: exergy analysis; organic Rankine cycle; photovoltaic; thermal collector PV; solar thermal; analiza egzergii; cykl Rankine`a; fotowoltaika; kolektor PV/T; energia słoneczna